Internalizing the Value of Qaulan Karîmain Shaping the Character of Polite Communication in the Digital Era: A Thematic Interpretation Study - Muhammad Khoiruddin; Mohamad Rifqy Roosdhani; Ali Ali; Nurul Komariyatin; Nurul Huda (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This research is motivated by the socio-religious paradox in Indonesia, where strong religious identities conflict with low levels of politeness in the digital space. Digital Civility Index data shows the rampant dehumanization, hate speech, and cyberbullying, which indicates the failure to internalize moral values into computer-mediated communication behavior. The main purpose of this research is to formulate a model for internalizing the value of Qaulan Karîma as a theoretical and practical solution to the ethical crisis. The method used is a qualitative-based literature study with a Thematic Tafsir (Maudhu'i) approach. The analysis was carried out by exploring Qur'anic verses related to Qaulan Karîmaand relating them to the dynamics of Computer-Mediated Communication (CMC) theory. The results of the study show that the internalization of values must be carried out through three transformative stages: cognitive-literative, affective-spiritual (through the concept of Digital Muraqabah), and psychomotor-habitual. The resulting communication typology comprises preventive, curative, and educational domains that serve as moral filters amid platform anonymity. This finding confirms that the character of polite communication is formed only when the value of the Qur'an extends beyond textual knowledge, becoming ingrained as a reflex of cyber behavior. The implications of this study demand reform of national digital literacy policies so that they do not focus solely on technical skills but also integrate the depth of religious spirituality into the character education curriculum. This model is expected to help build a more dignified, inclusive, and responsive Indonesian cyber ecosystem to address future challenges posed by information technology disruption.